(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The methods of digital pedagogy provide great opportunities for the development of the creative thinking potential of students. Through these methods, students can be encouraged to advance creative ideas, solve problems in a new way, and realize their own creative potential.